Iraq : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This staff report on Iraq's 2013 Article IV Consultation highlights economic policies and development. Risks to the macroeconomic outlook remain high. The risks can translate into lower oil revenues, deterioration in the fiscal position, pressures to use Central Bank of Iraq reserves for fiscal purposes leading to depreciation pressures, and higher inflation. Policies to mitigate their impact include strengthening fiscal institutions and oil revenue management, improving monetary policy transmission, and reducing the economy's dependence on the oil sector. The authorities depend solely on fiscal policy to address these vulnerabilities, underscoring the need for the authorities to urgently build up sufficient fiscal buffers, since Iraq's fiscal and external performance is very sensitive to fluctuations in oil prices.